Characterization and recovery of gold associated with fine, activated carbon - J. Rowe (The Southern African Institute of Mining and Metallurgy, 2009)
The attrition of activated carbon, and the loss of gold associated with it, is of significant economic importance to the operation of a CIP/CIL circuit The focus of this study was on activated carbon recovered from an elution circuit which was deemed too fine for reuse. Results of cyclosizer and laser particle size analysis identified that most of the carbon was contained in the larger size fraction suggesting formation by abrasion. Digestion and AAS analysis of the individual size fractions identified a disproportionate concentration of gold in the finer size fractions which was identified by scanning electron microscopy to be due to the presence of fine metallic gold formed as a result of the acid washing process. Attempts to strip the remaining gold using sodium hydroxide or sodium sulphide based solutions proved unsuccessful due to poor elution efficiencies and re adsorption of gold. Upgrading of the material by froth flotation was also investigated using various conventional flotation reagents which had some success in concentrating the free metallic gold, however, grade and/or recoveries were considered less than desirable. Greater success was ultimately found in the transfer of gold from the fine carbon material onto coarser virgin activated carbon using a caustic cyanide solution. Sodium sulphide, sodium chloride and ammonium chloride based solutions were also trialled but proved less successful owing to their inability to mobilise metallic gold or gold cyanide species. Repetition of the transfer process proved capable of stripping 97% of the gold contained on the carbon fines for abed volume ratio of 6:1.